Infant and young child feeding practice status and its determinants in UAE: results from the MISC cohort - Mona Hashim; Rana Rizk; Nada Abbas; Dana N. Abdelrahim; Hayder Hasan; Reyad S. Obaid; Hessa Al-Ghazal; Marwa Al Hilali; Farah Naja; Hadia Radwan (International Breastfeeding Journal)
Abstract Background To evaluate breastfeeding and complementary feeding practices and their determinants among infants and young children in the United Arab Emirates using the 2021 WHO/UNICEF IYCF guidelines. Methods The Mother and Infant Study Cohort (MISC), is a prospective study of mothers recruited in their third gestational trimester and followed with their infants up to 18 months of age (n = 167). Data were collected at 3rd trimester, delivery, 2, 6, 12, and 18 months postpartum via questionnaires, review of medical records, anthropometric measurements, and 24-hour dietary recalls of the child’s intake at 6, 12, and 18 months. Descriptive statistics and multiple logistic regressions were used to report on feeding practices and their determinants. Results Ever breastfeeding, Early initiation of breastfeeding, and exclusive breastfeeding under 6 months were reported by 84.3%, 99.4%, and 32.9% of participants, respectively. Of children, 96.4% consumed solid foods at 6–8 months; 68.7% and 44.7% continued to be breastfed at 12 and 18 months, respectively. Despite improvement with age; several complementary feeding indicators remained suboptimal at 18 months: Minimum Dietary Diversity: 40.4%, Minimum Meal Frequency: 56.7%, Minimum Acceptable Diet: 23.1%, Sugar-Sweetened Beverages, 26.9%, Zero Vegetables and Fruits: 28.8%, Unhealthy Food Consumption: 65.4%. After adjustment, multiparous mothers had higher odds of exclusive breastfeeding, whereas pregnancy complications were associated with lower odds of exclusive breastfeeding. Continued breastfeeding at 18 months was associated with older age among mothers and lower income. Among the factors associated with complementary feeding indicators were higher physical activity and Minimum Dietary Diversity. While Gestational Diabetes Mellitus, Sugar-Sweetened Beverages, and higher education were associated with lower odds of Zero Vegetables and Fruits, and a higher income was associated with lower Unhealthy Food Consumption. Conclusions This study reported good rates of Early initiation of breastfeeding and ever-breastfeeding, yet suboptimal exclusive breastfeeding and complementary feeding. The identified risk factors for inappropriate practices could be used to guide nutrition interventions and public health programs in the United Arab Emirates.